Digital Transformation Drives Banking Financial Performance Evidence from Indonesia: Transformasi Digital Mendorong Kinerja Keuangan Perbankan di Indonesia - Nova, Amellia; Darmayanti, Novi; Rosyida, Isnaini Anniswati (Universitas Muhammadiyah Sidoarjo, 2026)
This study examines determinants of banking financial performance in the context of post-pandemic recovery and digital economy transition. General Background: The Indonesian banking sector experienced structural shifts during 2021–2024 due to digitalization, regulatory changes, and competitive pressures. Specific Background: Strategic Performance Measurement System (SPMS), Enterprise Risk Management Disclosure (ERMD), and digital transformation are considered key managerial and governance mechanisms influencing financial outcomes. Knowledge Gap: Prior studies largely analyze these variables separately, with limited integrated evidence and inconsistent findings, particularly in Indonesian banking during the post-pandemic period. Aims: This study aims to analyze the simultaneous and partial relationships of SPMS, ERMD, and digital transformation on financial performance, proxied by Return on Assets (ROA), with firm size as a control variable. Results: Using panel data regression with 180 observations from 45 banks, the findings reveal that SPMS and ERMD do not show significant relationships with financial performance, while digital transformation demonstrates a significant positive relationship. Simultaneously, all variables contribute significantly, although the explanatory power remains limited (Adjusted R² = 0.0921). Novelty: This study integrates strategic measurement, risk disclosure, and digital capability within a single analytical framework during the 2021–2024 transition period. Implications: The findings highlight digital capability as a dominant driver of banking profitability, suggesting that integrated digital transformation strategies are essential for sustaining competitiveness in the digital economy. Highlights• Digital capability shows the strongest statistical relationship with profitability indicators• Disclosure-based mechanisms display non-significant statistical relationships• Combined model explains financial variation despite limited explanatory power KeywordsDigital Transformation; Financial Performance; Banking Sector; Enterprise Risk Management Disclosure; Strategic Performance Measurement System